Trocas turbulentas de escalares acima e no interior de uma floresta de araucária no sul do Brasil - Oliveira, Pablo Eli Soares de (2011)
Turbulent exchange of scalars is analyzed for a year of turbulence data, above and within an Araucaria Forest in southern Brazil. Sensible and latent heat fluxes, as well as CO2 fluxes are calculated by the eddy covariance method and analyzed in terms of the seasonal variation of their daily cycles. Diurnal and nocturnal vertical velocity spectra, sensible and latent heat flux cospectra andCO2 flux cospectra are also calculated using the multiresolution decomposition in both levels. Seasonal variations in spectra and cospectra are analyzed, as well as nocturnal and diurnal differences and the differences between the levels. Emphasis is given to the mechanisms controlling the connection between the two levels and its implications on scalar flux quantification. All scalars show a clear seasonality along the year. CO2 fluxes are negative during the day and positive at night above the canopy. In the lower level, CO2 fluxes are mostly positive along the day, with the same magnitude observed in the upper level during the night, indicating that nocturnal emission is dominated by lower levels of the forest, originated predominantly close to the floor. This fact is attributed to periods with low turbulence intensity when CO2 respired accumulates near the surface and gets transported horizontally, being captured by the lower system but missed by the upper one. Sensible heat fluxes show opposite signal in both levels, being more intense above the canopy, with a small contribution from the lower level to the total flux due the low penetration of radiation within the canopy. Latent heat fluxes are mostly positive in both levels, with the larger values above the canopy, indicating that the canopy is responsible for most of the forest evapotranspiration. Analysis of multiresolution spectra and cospectra shows that, above the canopy, the nocturnal time scale of turbulent exchange is smaller than during the day. Between the two levels, the opposite occurs, and the time scale within the canopy shifts towards the larger scales. There is a connection between the two levels, and not only in the highly turbulent nights, but also intermittently in more stable conditions. During these events of connection, the turbulence time scales above and within the canopy become very similar, and the differences in scalar concentration vanish. When calm periods precede highly turbulent ones, a good portion of scalars that accumulated at the canopy during the earlier calm period gets transferred by intermittent events. We show that this process is systematic enough to affect the overall fluxes when the turbulence history is taken into account, and the effect of this process is more intense for CO2 fluxes than for energy fluxes.